Familial Focal Congenital Hyperinsulinism - Ismail, Dunia (Endocrine Society, 2011)
BACKGROUND: Congenital hyperinsulinism (CHI) is a cause of persistent hypoglycemia. Histologically, there are two subgroups, diffuse and focal. Focal CHI is a consequence of two independent events, inheritance of a paternal mutation in ABCC8/KCNJ11 and paternal uniparental isodisomy of chromosome 11p15 within the embryonic pancreas, leading to an imbalance in the expression of imprinted genes. The probability of both events occurring within siblings is rare. AIM: We describe the first familial form of focal CHI in two siblings. PATIENTS AND METHODS: The proband presented with medically unresponsive CHI. He underwent pancreatic venous sampling and Fluorine-18-L-dihydroxyphenylalanine positron emission tomography scan, which localized a 5-mm focal lesion in the isthmus of the pancreas. The sibling presented 8 yr later also with medically unresponsive CHI. An Fluorine-18-L-dihydroxyphenylalanine positron emission-computerised tomography scan showed a 7-mm focal lesion in the posterior section of the head of the pancreas. Both siblings were found to be heterozygous for two paternally inherited ABCC8 mutations, A355T and R1494W. Surgical removal of the focal lesions in both siblings cured the Hyperinsulinaemic hypoglycaemia. CONCLUSION: This is the first report of focal CHI occurring in siblings. Genetic counseling for families of patients with focal CHI should be recommended, despite the rare risk of recurrence of this disease.